Good victims: the political as a feminist question - Krystalli, Roxani (Oxford studies in gender and international relations, 2024)
In Good Victims, Roxani Krystalli investigates the politics of victimhood as a feminist question. Based on in-depth engagement in Colombia over the course of a decade, Krystalli argues for the possibilities of politics through, rather than in opposition to, the status of "victim." Encompassing acts of care, agency, and haunting, the politics of victimhood entangle people who identify as victims, researchers, and transitional justice professionals. Krystalli shows how victimhood becomes a pillar of reimagining the state in the wake of war, and of bringing a vision of that state into being through bureaucratic encounters. Good Victims also sheds light on the ethical and methodological dilemmas that arise when contemplating the legacies of transitional justice mechanisms.